Phonetic Variation in South Bolivian Quechua: Dorsal Lenition and Vowel Deletion - Gallagher, Gillian (2025)
This article presents a description of two areas of phonetic variation in South Bolivia Quechua, through the analysis of six interviews with bilingual Quechua-Spanish speakers. The first study describes variable lenition in plain and aspirated dorsal stops k q kh qh (e.g., the pronounciation of paykuna ‘they’ as [pajkuna] or [pajɣuna]), and shows that lenition of q is frequent and general while lenition of k kh and qh is more restricted. Lenition of k is found only in a single phonetic context and lenition of kh is found in only a single root, mikhu- ‘to eat’, in the productions of a few speakers. Lenition of qh is general, but less frequent than lenition of q. The second study presents a quantitative analysis of word-final vowel deletion (e.g., chaypi ‘there’ can be pronounced as [ʧajpi] or [ʧajp]), and shows that deletion is more frequent in phrase-final position and in the context of voiceless consonants. It is noted throughout the presentation that variation is structured, in that the production of a sound varies systematically according to phonetic context, morpheme and/or speaker. The novel contribution of this work to the study of Quechua languages is a more complete description of dorsal consonant lenition and the first description of vowel deletion in this dialect, based on a phonetic analysis of recorded natural speech.